Wellbeing in Trafficked Victims: An Intervention Study - Dhoundiyal, Ananya; Karalam, Sheeja (Journal of Social Work Education and Practice, 2023)
It is sad that India supplies receives and is the transit point for many forms of Human Trafficking. 'Adolescent girls' who constitute a large number of trafficked victims are gravely impacted physically, psychologically and socially on account of trafficking. These girls are in dire need of care and protection. They need to be given unconditional love and attention to surmount the trauma inflicted upon them. However, it is noted that there is great lack of requisite services, information and attitude in the support mechanism system which is a precondition for helping the victims develop a positive outlook towards life.It is in this backdrop that an intervention study was conducted to assess the wellbeing of rescued girls admitted to the Government Children's Home. An attempt was made to develop and implement an intervention for the benefit of the rescued girls and assess its effectiveness. The study was conducted on a total of 15 girls aged between 12-18 years residing in the Girls Home, Bengaluru. Single group pre-post-test design was used for the Study. A standardized Wellbeing Scale was used for data collection. A multi-component intervention was developed based on the pre-test which consisted of 8 days intense interactive sessions on Physical wellbeing, Emotional wellbeing, Social Skills and General Orientation. A paired t-test was performed which revealed a significant change (P=.000) in wellbeing scores after the intervention. It can thus be deduced that the multi-component intervention tailored for girls affected by sexual abuse proved to be effective in improving their wellbeing.
Keywords: Human Trafficking; Adolescent Girls; Wellbeing; Intervention